2015
DOI: 10.3233/ch-151935
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of gentamicin dioctyl sulfosuccinate loaded poly(trimethylene carbonate) matrices intended for the treatment of orthopaedic infections

Abstract: Lipophilic GEN-AOT was at least as potent as GEN-SULPH. For S. epidermidis it was even more potent than GEN-SULPH. More than 50% fibroblast cell viability was maintained at bactericidal concentration for both bacterial strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…AOT—unlike GentS—does not have any amine groups in its structure, which can be assigned to, e.g., the absorption band with maximum at 1620 cm −1 . This and a few other bands marked by a yellow color in Figure 1 in both GentS and GentAOT spectra, and not present in AOT spectra, consists of a sufficient proof of antibiotic modification according to Boo et al [ 33 ] who got similar results.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…AOT—unlike GentS—does not have any amine groups in its structure, which can be assigned to, e.g., the absorption band with maximum at 1620 cm −1 . This and a few other bands marked by a yellow color in Figure 1 in both GentS and GentAOT spectra, and not present in AOT spectra, consists of a sufficient proof of antibiotic modification according to Boo et al [ 33 ] who got similar results.…”
Section: Resultssupporting
confidence: 62%
“…The bactericidal properties of GentAOT in relation to S. aureus (NCTC 12973) were already confirmed by Boo et al [ 33 ] who concluded that the efficiency of GentAOT in inhibiting the growth of this strain of bacteria does not change during the manufacturing process. In our study, the efficiency against MRSA (ATCC BAA 1681) was slightly higher, as the inhibition zone of 10 µg of GentAOT was 21 mm, whilst for the substrate GentS it was 20 mm ( Figure 2 E).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…With a view to increase the loading of tobramycin within the PLGA nanoparticles, we investigated the co-formulation of the drug with a surfactant (AOT) that has previously been used to increase the loading of other hydrophilic drugs within PLGA nanoparticles. This was achieved by increased lipophilicity of the drug-AOT complexes generated through ionic interactions; in this case the anionic sulfonate of the AOT and the cationic amine of tobramycin) [54,55,56]. To assess the lipophilicity of the tobramycin-AOT complexes, the extraction of tobramycin into organic solvents was assessed by a variety of methods.…”
Section: Resultsmentioning
confidence: 99%